Clinical implications of late-onset right ventricular failure after implantation of a continuous-flow left ventricular assist device as bridge to transplantation. (30th March 2021) - Ruiz-Cano, Maria J; Ramazyan, Lylit; Schramm, Renné; Lauenroth, Volker; Paluszkiewicz, Lech; Rojas, Sebastian; Gummert, Jan; Morshuis, Michiel
Abstract: OBJECTIVES: The development of late-onset right ventricular failure (LoRVF) that occurs months after a continuous-flow left ventricular assist device (LVAD) is implanted is a clinical problem that warrants investigation. Our goal was to study the incidence, clinical manifestations and prognosis of LoRVF in a population of patients who received an LVAD as bridge to transplantation. METHODS: Data were analysed from 97 consecutive patients who received an LVAD as bridge to transplantation and underwent a right heart catheterization at least 3 months after receiving an LVAD implantation. LoRVF was defined if both haemodynamic criteria of a central venous pressure >16 mmHg and a cardiac index <2.3 l/min/m 2 were present. Clinical and echocardiographic variables, hospitalizations for heart failure and survival were compared between patients with and without LoRVF. RESULTS: LoRVF was diagnosed in 13% of patients after a median time of 11 months. Patients with LoRVF presented preoperative worse right ventricular (RV) dilatation and severe tricuspid regurgitation. LORVF was also associated with postoperative RV dilatation, moderate to severe tricuspid regurgitation and lower tricuspid annular plane systolic excursion. LoRVF resulted in increased brain natriuretic peptide levels and the need for diuretics, lower haemoglobin levels and a higher rate of atrial fibrillation and gastrointestinal bleeding. The rate of hospitalizations for heart failure in patients with LoRVF was 46%, and 15% required an urgent transplantation due to refractory RV failure. LoRVF decreased global survival and survival free from hospitalizations for heart failure ( P < 0.0001). CONCLUSIONS: LoRVF after the implantation of an LVAD as bridge to transplantation is associated with higher morbidity and lower survival. The results suggest that the routine use of a right heart catheterization and transthoracic echocardiography may contribute to an early diagnosis before further severe complications due to refractory RV failure might occur. ID number of the IRB approval: AZ-2019-521 on 10 July 2019.